IMPROVEMENT OF THERMAL TREATMENT OF MATERIALS OF PROCESS MACHINE PARTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In world practical person is conducted big volume of the research work, directed on development of the technology and technologies, providing efficient using the modern achievements of the science and technology, modernization existing equipment and introduction them in production. In this sphere development and improvement of the complex of the technical facilities for fabrication of the main detail’s worker organ processing machines with the most efficiency gain special importance.